ELASTIC DEFORMATIONS IMPACT IN ELEMENTS OF THE RAIL FASTENING, TYPE КПП-5 ON A SIZE OF PRESSING FORCE OF THE RAIL TO THE SUBRAIL BASIS - Nastechik, N. P.; Marcul, R. V.; Savytskyi, V. V. (Science and Transport Progress, 2015)
Purpose. The railway transport is one of the most important links in economy of Ukraine, and it is a basis of its transport system. As the majority of freight transportation of coal and metallurgical industry is conducted by railway transport, its effective use is a necessary condition of stabilization and development in economy of Ukraine. One of the strategic works connected with implementation of high-speed train service in Ukraine is the reliable work ensuring of connection of intermediate rail fastening during operation. For engineering works, according to the contents and repair of fastenings the considerable share of labor expenses during operation of a way is necessary. One of domestic intermediate fastenings which after long operational supervision has implemented into continuous operation is the fastening, type КПП-5. This fastening is a prototype of the Polish rail fastening type SB-3. After the long operation in fastenings, type KПП-5, a number of the shortcomings connected with premature refusal of its elements was revealed. This in generally is connected with intensive reduction of size of pressing force of a rail to the subrail basis. Therefore the purpose is the development of a technique and practical control devices concerning a condition of work of a rail fastening knot, type KПП-5 at operation. Methodology. The assessment of various factors impact at a size of pressing force of a rail to the subrail basis in the knot of a rail fastening, type KПП-5 at operation is the foundation of the research method. Findings. By means of the developed technique and practical control devices it was established: the general reduction of pressing force of a rail to the subrail basis during one mill. tons gross., taking into account influence of various factors, may constitute kN. Originality. Accordingly to the obtained results the author firstly described and expressed by empirical dependence the process of change of pressing force of a rail to a subrail basis in a fastening, type KПП-5 after the admission of T, one mill. tons gross. Practical value. The device design is developed for control of elastic properties and a numerical assessment of pressing force decrease of the terminal to a rail depending on the passed tonnage.